Method for evaluating the properties of materials used in additive manufacturing objects created by 3D printers

JP7642940B2Active Publication Date: 2025-03-11MAEDA CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021098434
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-14
Publication Date
2025-03-11
Estimated Expiration
2041-06-14

AI Technical Summary

Benefits of technology

【0020】 本発明に係る積層造形に用いる材料の性状評価方法によれば、テーブルフロー試験、コーンプランジャー試験、積層造形体の表面性状について求めた算術平均粗さにより、3Dプリンターで作成する積層造形体に用いる材料の性状を評価する。すなわち、大がかりな試験機器や複雑な工程を行うことなく、簡便な方法により3Dプリンターで作成する積層造形体に用いる材料の性状を評価することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642940000001
    Figure 0007642940000001
  • Figure 0007642940000002
    Figure 0007642940000002
  • Figure 0007642940000003
    Figure 0007642940000003
Patent Text Reader

Abstract

To evaluate properties (pumpability, self-standing and stackability) of a material using concrete, for use in a 3D printer.SOLUTION: A property evaluation method includes a pumpability appropriateness evaluation step (S1), a self-standing appropriateness evaluation step (S2) and a stackability appropriateness evaluation step (S3), The pumpability appropriateness evaluation step (S1) includes executing at least one of a table flow test or a cone plunger test and evaluating pumpability of a composite material based on whether or not the test result is within appropriate values. The self-standing appropriateness evaluation step (S2) includes executing the cone plunger test and evaluating the self-standing of the composite material based on whether or not the test result is within appropriate values. The stackability appropriateness evaluation step (S3) includes acquiring arithmetic mean roughness of the surface properties of an additive manufacturing body and evaluating the stackability of the composite material based on whether or not the test result is within appropriate values. The property evaluation method determines a material satisfying the appropriate values in all the appropriateness evaluation steps, as an appropriate material (S4).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for evaluating the properties of materials used in layered objects created by a 3D printer, and in particular to a method for evaluating the properties (physical properties) related to pumpability, self-supporting ability, and layerability of composite materials used to create layered objects by a 3D printer. [Background technology]

[0002] In recent years, in the construction industry both domestically and internationally, there has been progress in the development of additive 3D printers, a construction method that uses 3D printing technology to build additive objects (structures) by layering them. The materials used in additive 3D printers are basically cement-based materials, and mortar mixed in a mixer is pumped and supplied to the 3D modeling device. Construction using additive 3D printers allows structures to be layered without formwork, and is expected to have significant advantages over conventional concrete construction in terms of labor savings, design freedom, and safety.

[0003] In order to put this type of construction method into practical use in the future, in addition to developing and improving 3D printers, it will be necessary to consider factors such as the pumpability of the material, the ability of the material to stand on its own immediately after being ejected from the nozzle onto the additive manufacturing body (structure), and the surface properties of the laminated body after hardening.

[0004] To create an additively manufactured object (structure) with high construction accuracy, it is mainly necessary to develop materials with high self-supporting performance, and machines with high nozzle position accuracy, speed, and material discharge amount, etc. In addition, the structural performance is required so that the manufactured structure (structural form) can exert sufficient strength against various external forces.

[0005] Among the properties (physical properties) of the materials mentioned above, the cementitious material discharged from the nozzle has both the fluidity (pumpability) to flow smoothly inside the transport pipe and the shape stability to stand on its own and develop strength immediately after being discharged. Therefore, its physical properties are greatly influenced by various conditions such as the water addition rate, the time elapsed since mixing, and the transport speed.

[0006] Many techniques have been proposed for materials used in concrete 3D printers (see, for example, Patent Documents 1 to 4).

[0007] The technology described in Patent Document 1 relates to a cementitious material for additive lamination for creating a laminated structure by 3D printing technology. This cementitious material for additive lamination contains cement, fine aggregate, rapid hardening admixture, and retarder, and mortar or concrete is produced by kneading the cementitious material for additive lamination containing 20 parts by mass to 200 parts by mass of rapid hardening admixture per 100 parts by mass of cement. It is said that by using this mortar or concrete, a material with excellent fluidity and self-supporting stability can be provided in a concrete construction method using 3D printing technology.

[0008] The technology described in Patent Document 2 relates to a nozzle device for a 3D printer. This nozzle device for a 3D printer has a cylinder section that temporarily stores the viscous material supplied from a pump, a screw conveying section equipped with a screw that pushes out the viscous material in the cylinder section, and a nozzle section that is detachably attached to the tip of the screw conveying section. It is said that by using this nozzle device for a 3D printer, it is possible to supply a fixed amount of viscous material without being affected by the pulsation of the viscous material supplied from a viscous material supplying means such as a pump.

[0009] The technology described in Patent Document 3 relates to a cementitious material for three-dimensional modeling for construction. This cementitious material for three-dimensional modeling for construction contains cement, aggregate, a dispersant in which the mass ratio of a lignin sulfonic acid-based dispersant (R) and a melamine sulfonic acid-based dispersant (M) is R:M=100:80-400, a thickener, a setting retarder, amorphous calcium aluminosilicate containing 10-25% SiO2 in oxide equivalent, gypsum, and short fibers. It is said that by using this cementitious material for three-dimensional modeling for construction, it is possible to supply a constant amount of material and ensure a constant layering speed. In addition, it is said that since excellent self-supporting property and strength development are obtained, a large-sized modeling object can be constructed in a short time.

[0010] The technology described in Patent Document 4 relates to a cement composition for molding. This cement composition for molding contains at least 25-70% by mass of a cement-containing binder, 0.1-5% by mass of an admixture, and 25-70% by mass of fine aggregate. It is said that by using this cement composition for molding, it is possible to manufacture cementitious hardened bodies having delicate and diverse designs. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2020-200215 A [Patent Document 2] JP 2019-147338 A [Patent Document 3] JP 2018-140906 A [Patent Document 4] JP 2017-24979 A Summary of the Invention [Problem to be solved by the invention]

[0012] Currently, there are no tests officially defined by ISO, JIS, etc. for evaluating the properties of materials used in additively manufactured objects created by 3D printers. Furthermore, most conventional technology involves large-scale testing, which is not necessarily easy to use when considering the preparation of test specimens and loading equipment (this tendency is particularly noticeable in self-support evaluation tests). Furthermore, when checking changes over time, it is necessary to prepare a test specimen for each hour, and repeated measurements cannot be performed on the same sample, raising concerns about variability in the results.

[0013] In addition, the surface properties of the cured laminate vary depending on the composition of the materials, but it is not always possible to cut the cured body and observe the cross section to grasp the surface roughness. Furthermore, it is difficult to visually judge the difference in surface properties using a photograph of the surface of the laminate.

[0014] As such, the current situation is that the method for evaluating the physical properties of cement-based materials used in 3D printers has not yet been established. Therefore, it is necessary to use cement-based materials that are uniquely suited to each 3D printer, which is an issue.

[0015] The present invention has been proposed in consideration of the above-mentioned circumstances, and aims to provide a property evaluation method that can easily evaluate the properties (pumpability, self-supporting property, stackability) of materials used in 3D printers that use concrete. [Means for solving the problem]

[0016] The method for evaluating the properties of a material used in additive manufacturing created by a 3D printer according to the present invention (hereinafter, sometimes abbreviated as the method for evaluating the properties of a material used in additive manufacturing) has the following features in order to achieve the above-mentioned object. That is, the method for evaluating the properties of a material used in additive manufacturing according to the present invention is a method for evaluating the properties of a composite material used to create an additive manufacturing object by a 3D printer, and includes a pumpability aptitude evaluation step for evaluating the aptitude of pumpability, an independence aptitude evaluation step for evaluating the aptitude of independence, and a stacking aptitude evaluation step for evaluating the aptitude of stacking. Note that, as for the test itself in each evaluation step, each test is performed independently, but the order of execution of the steps related to each evaluation is arbitrary, and each evaluation step may be performed in parallel, or any evaluation step may be performed with priority.

[0017] The pumpability evaluation step is a step of evaluating the pumpability of a composite material by performing at least one of a table flow test and a cone plunger test and determining whether the test result is within a range of appropriate values. For example, the fluidity of a material is evaluated by at least one of a table flow test and a cone plunger test, and the pumpability of the composite material is evaluated based on the test value. Note that fluidity is a property that is correlated with pumpability.

[0018] The self-supporting property evaluation step is a step of evaluating the self-supporting property of the composite material based on whether the test result is within a range of appropriate values ​​by performing a cone plunger test. For example, the yield stress (shear yield stress) of the layered object is obtained by the cone plunger test, and the self-supporting property of the composite material is evaluated based on the yield stress.

[0019] The stackability evaluation step is a step of determining the arithmetic mean roughness of the surface properties of the layered object, and evaluating the stackability of the composite material based on whether the arithmetic mean roughness is within a range of appropriate values. For example, the cross-sectional shape of the layered object is recognized to determine the arithmetic mean roughness, and the stackability of the composite material is evaluated based on the arithmetic mean roughness. Furthermore, the stackability evaluation step preferably evaluates the stackability of the composite material by taking into account an evaluation value of the aesthetics of the cross-sectional shape of the layered object. Effect of the Invention

[0020] According to the method for evaluating the properties of a material used in additive manufacturing of the present invention, the properties of a material used in an additive manufacturing object created by a 3D printer are evaluated by a table flow test, a cone plunger test, and the arithmetic mean roughness determined for the surface properties of the additive manufacturing object. In other words, it is possible to evaluate the properties of a material used in an additive manufacturing object created by a 3D printer by a simple method without using large-scale testing equipment or complex processes. [Brief description of the drawings]

[0021] [Figure 1] 1 is an explanatory diagram showing a procedure of a method for evaluating the properties of a material used in additive manufacturing according to an embodiment of the present invention. [Diagram 2] Schematic diagram of a cone plunger testing machine (overall view, partially enlarged view). [Diagram 3] FIG. 2 is an explanatory diagram showing the change in yield stress over time in a cone plunger test. [Figure 4] FIG. 2 is an explanatory diagram showing the relationship between yield stress and self-supporting property. [Diagram 5] FIG. 1 is an explanatory diagram showing the relationship between the results of a conventional self-supporting evaluation test and the results of a cone plunger test. [Figure 6] FIG. 4 is an explanatory diagram showing a cross-sectional shape of a layered object. [Figure 7] FIG. 4 is an explanatory diagram showing the arithmetic mean roughness of the surface of a layered object. [Figure 8] FIG. 1 is an explanatory diagram of the material components used in the test. [Figure 9] FIG. 1 is an explanatory diagram showing the composition (mixture) of materials used in the test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the method for evaluating the properties of a material used in additive manufacturing according to the present invention will be described with reference to the drawings. Figures 1 to 9 are diagrams for explaining the method for evaluating the properties of a material used in additive manufacturing according to an embodiment of the present invention. Figure 1 is an explanatory diagram showing the procedure of the method for evaluating the properties of a material used in additive manufacturing, Figure 2 is a schematic diagram of a cone plunger tester (overall view (a), partial enlarged view (b)), Figure 3 is an explanatory diagram showing the change over time in yield stress by a cone plunger test, Figure 4 is an explanatory diagram showing the relationship between yield stress and self-supporting property, Figure 5 is an explanatory diagram showing the relationship between the results of a conventional self-supporting property evaluation test and the results of a cone plunger test, Figure 6 is an explanatory diagram showing the cross-sectional shape of an additive manufacturing body, Figure 7 is an explanatory diagram showing the arithmetic mean roughness of the surface of an additive manufacturing body, Figure 8 is an explanatory diagram of the material components used in the test, and Figure 9 is an explanatory diagram showing the blending (mixture) of the materials used in the test.

[0023] <Outline of the method for evaluating the properties of materials used in additive manufacturing> The method for evaluating the properties of materials used in additive manufacturing according to an embodiment of the present invention is a method for easily evaluating the performance (pumpability, self-supporting property, stackability) of materials used in 3D printers that use concrete. Simple tests are performed for each evaluation item, and the appropriateness of the material is determined by clearing the threshold value for each 3D printer used. In the following description, the composite material refers to the printing material after being ejected from the nozzle of the 3D printer.

[0024] As shown in Fig. 1, the method for evaluating the properties of a material used in additive manufacturing according to an embodiment of the present invention includes a pumpability evaluation step (S1) for evaluating the pumpability, a self-supporting property evaluation step (S2) for evaluating the self-supporting property, and a stacking property evaluation step (S3) for evaluating the stacking property. Note that Fig. 1 shows that the pumpability evaluation step (S1) and the self-supporting property evaluation step (S2) are performed in parallel, and the stacking property evaluation step (S3) is performed after the material is determined to be suitable in both the evaluation steps. However, the pumpability evaluation step (S1), the self-supporting property evaluation step (S2), and the stacking property evaluation step (S3) are independent evaluation steps, and the order of execution does not matter. Note that the "no matter the order of execution of each evaluation step" refers to the order of the steps, and the tests themselves in each evaluation step are performed independently. Then, in all of the suitability evaluation steps, namely the pumpability suitability evaluation step (S1), the self-supporting property suitability evaluation step (S2), and the stackability suitability evaluation step (S3), the material that falls within the suitability value range is determined to be a suitable material to be used in additive manufacturing (S4).

[0025] <Pumpability suitability evaluation process> The pumpability evaluation step is a step of evaluating the pumpability of the composite material based on whether or not the test results are within an appropriate range by performing at least one of a table flow test and a cone plunger test. Specifically, the fluidity of the material (a property that is correlated with pumpability) is evaluated by at least one of a table flow test and a cone plunger test, and the pumpability of the composite material is evaluated based on the test values.

[0026] The table flow test is a test that conforms to JIS R 5201, which specifies the physical testing method for cement, and is specifically a test to measure the fluidity of mortar. In the table flow test, the sample is filled in two layers in a flow cone placed on a table, and each layer is poked 15 times over the entire surface with a poker. The flow cone is then removed, and the flow table is moved up and down, allowing the sample to fall 15 times in 15 seconds. The diameter of the expanded sample is then measured in the direction that is deemed to be the largest and in the direction perpendicular to this, and the average value is taken as the flow value (mm).

[0027] The flow value obtained by the table flow test indicates the fluidity of the material, and the pumpability of the composite material is evaluated based on this flow value. In the pumpability evaluation, if the flow value is within the appropriate range, the material is judged to be appropriate for use in additive manufacturing, and if the flow value is outside the appropriate range, the material is judged to be inappropriate for use in additive manufacturing.

[0028] In the present invention, as a test method in the pumpability evaluation step, not only the table flow test but also the test results of the cone plunger test can be used. That is, the pumpability of the composite material is evaluated by performing the cone plunger test instead of the table flow test or by performing the cone plunger test in addition to the table flow test. The cone plunger test will be described in detail later.

[0029] <Self-reliability assessment process> The self-supporting property evaluation step is a step of evaluating the self-supporting property of the composite material based on whether the test result is within a range of appropriate values ​​by performing a cone plunger test. Specifically, the yield stress of the layered product is obtained by the cone plunger test, and the self-supporting property of the composite material is evaluated based on the yield stress.

[0030] <Cone plunger test> The cone plunger test is a test that conforms to JIS R 5201, which specifies the physical testing method for cement. More specifically, it is a test that uses a Vicat needle device to measure the standard softness, initial setting time, and final setting time of cement.

[0031] In the cone plunger test of this embodiment, the yield stress for evaluating the self-supporting property of the composite material to be tested can be easily obtained by using a cone plunger tester 10 shown in FIG. 2. In the cone plunger tester 10, as shown in FIG. 2, an arm 12 is attached to the upper part of a base 11. A support rod 14 is attached to the arm 12 by a jig 15 so as to be movable up and down. A cone 13 is attached to the tip (lower end) of the support rod 14. By operating the jig 15, the support rod 14 can be set to a state in which it is fixed to the arm 12 and a state in which it is released from the fixation to the arm 12 and the support rod 14 falls freely. Then, a sample 20 is placed on the base 11, and the cone 13 is allowed to fall freely according to the following test procedure, and the yield stress is measured based on the depth to which the cone 13 penetrates into the sample 20.

[0032] The cone plunger test is carried out according to the following procedure. First, the sample 20 is packed into a mold of φ170mm × H40mm, and the cone 13 with a mass of 893.2g and a tip angle of 30° is allowed to penetrate by free fall. As shown in Figure 2, the yield stress τ0 [Pa] can be calculated from the penetration depth h [m] when the cone 13 with a tip angle θ [°] and a mass m [kg] is penetrated into the sample 20, using the following formula (1). Note that g [m / s 2 ] is the acceleration due to gravity. τ0=m×g×(cosθ) 2 / πh 2 ×tanθ ··· Equation (1)

[0033] The cone plunger test was performed twice for each material mix (mixture), and was performed every 5 minutes from 10 to 60 minutes after mixing. The penetration depth was measured with a vernier caliper using the jig 15 attached to the cone plunger tester 10 as a guide. 1L of the sample 20 was mixed using a mortar mixer, and packed into a formwork placed on a glass plate in two layers, and each layer was poked 60 times with a ramming rod, and the surface was leveled. After the sample 20 was packed into the formwork, a glass plate was placed on top and the top and bottom were inverted. In other words, the test surface into which the cone 13 penetrates was the bottom surface when the sample 20 was packed into the formwork.

[0034] The relationship between the time elapsed after mixing obtained from the cone plunger test and the yield stress calculated by formula (1) is shown in Figure 3. For all materials of the mix (mixture) used in the test, the yield stress increased with the time elapsed after mixing. As is clear from Figure 3, the standard mortar, S40-F2.0, and S60-F1.25 showed similar yield stresses, and only S60-F2.0C showed a value higher than the other mixes (mixtures). The material components and mixes (mixtures) used for each sample 20 will be described later.

[0035] Figure 4 shows the relationship between yield stress and self-supporting ability. As is clear from Figure 4, a correlation is observed between yield stress and self-supporting ability. Therefore, the self-supporting ability of a material can be determined from the yield stress determined by the cone plunger test, and the self-supporting ability of a composite material is evaluated based on this yield stress. In evaluating self-supporting ability, if the yield stress is within the appropriate range, the material is judged to be appropriate for use in additive manufacturing, and if the yield stress is outside the appropriate range, the material is judged to be inappropriate for use in additive manufacturing.

[0036] <Conventional Independence Assessment Tests> In the present invention, the self-supporting property of a composite material is evaluated by a cone plunger test, but generally, the self-supporting property of a composite material is evaluated by a compression test (hereinafter referred to as a conventional self-supporting property evaluation test). This conventional self-supporting property evaluation test is a test method in which fresh mortar is loaded by a compression tester in order to evaluate the self-supporting property of a sample immediately after mixing. Although not shown, in the conventional self-supporting property evaluation test, a test specimen is prepared by pouring mortar into a formwork and demolding it. After the demolding, the test specimen is left to stand for a predetermined time, and loading is performed using a screw-type manual loading tester. The displacement measured in the conventional self-supporting property evaluation test is measured at four corners of the loading plate, and the average value is obtained. As a method for evaluating the self-supporting property, a test is performed every 15 minutes from 15 minutes to 90 minutes after mixing, and the relationship between stress and strain is obtained.

[0037] <Correlation between the results of conventional self-support evaluation tests and cone plunger tests> The conventional self-supporting evaluation test can obtain the Young's modulus of the material, and the cone plunger test can obtain the yield stress of the material. Figure 5 shows the relationship between the results of the cone plunger test and the results of the conventional self-supporting evaluation test. As is clear from Figure 5, the calculated yield stress is correlated with the resistance to deformation obtained from the conventional self-supporting evaluation test.

[0038] <Lamination Appropriateness Evaluation Process> The stackability suitability evaluation step is a step of determining the arithmetic mean roughness of the surface properties of the layered object, and evaluating the stackability of the composite material based on whether the arithmetic mean roughness is within a range of suitable values. Specifically, the cross-sectional shape of the layered object is recognized to determine the arithmetic mean roughness, and the stackability of the composite material is evaluated based on the arithmetic mean roughness. The arithmetic mean roughness of the surface properties of the layered object indicates the degree of distortion of the surface of the layered object (unevenness from the center), making it possible to evaluate the suitability of the stackability.

[0039] To determine the arithmetic mean roughness, a laminate is cut out from the composite material to be used as the test specimen, the cross-sectional shape is obtained as coordinates, and the arithmetic mean roughness Ra of the general part excluding 50 mm from the top and bottom of the laminate is obtained in accordance with JIS B 0601: 2013, to evaluate the surface quality of the test specimen (laminated object).In addition, if it is difficult to cut out the laminate, the coordinates of the unevenness on the surface of the laminate are obtained manually or by laser scanning, Ra is obtained, and the surface quality of the test specimen (laminated object) is evaluated.

[0040] That is, as shown in Figure 6, the cross-sectional shape of the laminate was obtained as coordinates, and the arithmetic mean roughness Ra of the general part excluding 50 mm from the top and bottom of the laminate was calculated and evaluated in accordance with JIS B 0601:2013. The measured arithmetic mean roughness is shown in Figure 7. In evaluating laminateability, if the arithmetic mean roughness is within the appropriate range, it is judged to be a suitable material for additive manufacturing, and if it is outside the appropriate range, it is judged to be an inappropriate material that cannot be used for additive manufacturing.

[0041] <Aesthetic evaluation> In the lamination suitability evaluation process, it is preferable to evaluate the lamination of the composite material by taking into account the evaluation value of the aesthetics of the cross-sectional shape of the laminated object. In other words, the lamination suitability is judged by setting a threshold value for the arithmetic mean roughness. However, there are cases where a shape lacking aesthetic stability is evaluated as having high artistic quality, so rather than simply evaluating stability alone, it is also possible to assign evaluation points such as ○ points for stability and △ points for artistic quality. For example, image recognition is performed, and the relationship between the evaluation value of the cross-sectional shape and the aesthetics of the recognized image data is machine-learned to calculate the evaluation points for each laminate item formed.

[0042] Specifically, a plurality of evaluators capable of performing reliable aesthetic evaluations are asked to perform aesthetic evaluations on the same cross-sectional shape and give evaluation points, and the image data of the cross-sectional shape and the average evaluation points given by each evaluator are machine-learned to obtain reference data for the aesthetic evaluation points for the cross-sectional shape. After that, the cross-sectional shape of the layered object to be evaluated is image-recognized to obtain image data, and the image data is compared with the reference data of the aesthetic evaluation points obtained by machine learning to calculate the aesthetic evaluation points for the layered object to be evaluated. In addition, it is preferable to generate reference data by classifying the attributes of the evaluators of the aesthetic evaluation points into engineers, artists, any ordinary person, age group, nationality, etc., or by classifying the attributes of the layered object to be evaluated into civil engineering structures such as houses, sports facilities, libraries and museums, meeting places, benches, objets d'art, and bridges. That is, reference data is generated based on preferences related to the attributes of the evaluators and the intended use related to the attributes of the layered object, and the aesthetic evaluation points suitable for the layered object to be evaluated are calculated by using each reference data alone or in combination.

[0043] <Sample (test piece)> The test results for each of the above-mentioned evaluation methods are explained below. In the tests for each evaluation method, materials with the following mix (mixture) were used as samples (test specimens) (standard mortar, S40-F2.0, S60-F1.25, S60-F2.0C). A premix material (P) with a proven track record of layering was adopted as the standard cement-based material, and used at W / P = 14.75%. The specifications of the materials used for the samples (test specimens) and the mix (mixture) of each sample (test specimen) are shown in Figures 8 and 9.

[0044] The cementitious material to be evaluated was fiber-reinforced concrete (FRCC), and high-early-strength Portland cement (C) and silica fume (SF) were used as binders (B). Silica sand No. 7 was used as fine aggregate (S), and wollastonite (Wo), a fibrous mineral, was used as part of the fine aggregate.

[0045] The target reinforcing fiber content was 2.0 vol.%, the water-to-binder ratio (W / B) was fixed at 30%, and the binder was 85% C and 15% SF. Wo was mixed as a 10% replacement for S, and PE fiber was added as an external ratio to the kneaded volume. When adding cellulose nanofiber (CNF), a 0.05% solution was prepared in advance by dispersing CNF gel using a blender or homogenizer (oscillation frequency 21 kHz ± 1 kHz). The solution was then used as the kneading water so that the CNF was 0.005% of the binder.

[0046] <Thresholds in each evaluation step> In each evaluation process, the suitability of the material is judged based on whether the test results are within the appropriate range. In other words, if all test results are within the appropriate range, the material is judged to be suitable for use in the layered object created by the 3D printer. Below, an example of the evaluation threshold value in each evaluation process is explained, but the threshold value cannot be uniformly specified depending on the properties of the layered object to be created (purpose of use, size, shape, etc.), the environment during the creation of the layered object (temperature, humidity, etc.), and the equipment configuration of the 3D printer used (diameter and length of the pressure pipe, pressure pressure, etc.). Therefore, the threshold values ​​shown below are experimental threshold values, and when actually creating a layered object, the threshold values ​​are set appropriately depending on various factors.

[0047] <Examples of thresholds used in experiments> As described above, a correlation is found between the Young's modulus obtained from the conventional self-supporting evaluation test and the yield stress obtained from the cone plunger test. Therefore, based on the correlation, the thresholds of the pumpable material and the self-supporting material can be obtained. The thresholds of the self-supporting evaluation in this embodiment are, for example, a yield stress of 8.4 kPa (Young's modulus 67 kPa) or more at 5% deformation 10 minutes after kneading, a yield stress of 10.0 kPa (Young's modulus 101 kPa) or more at 5% deformation 20 minutes after kneading, and a yield stress of 11.6 kPa (Young's modulus 133 kPa) or more at 5% deformation 30 minutes after kneading. In addition, the threshold of the pumpability evaluation (pumpable material) is, for example, a yield stress of 18 kPa or less. In addition, the threshold of the lamination evaluation is, for example, Ra of 4.0 or less. As described above, the thresholds are examples in the experiment and are not limited to these values.

[0048] <Advantageous effects compared to conventional technologies> In the present invention, in particular, in the self-supporting evaluation step, the self-supporting evaluation by the cone plunger test is adopted instead of the self-supporting evaluation by the conventional self-supporting evaluation test. As described above, the yield stress calculated by the cone plunger test is correlated with the resistance to deformation obtained by the conventional self-supporting evaluation test.

[0049] The evaluation of self-supporting properties using the conventional self-supporting property evaluation test is a test method that is widely used both in Japan and overseas, but it is not necessarily a simple method when considering the preparation and loading of test specimens. In particular, when checking changes over time, it is necessary to prepare a test specimen for each hour, and repeated measurements cannot be performed on the same sample, which raises concerns about the variability in results. On the other hand, the cone plunger test makes it possible to measure changes over time with a single sample, making it possible to conduct the test even more easily than the conventional self-supporting property evaluation test.

[0050] That is, in the conventional self-support evaluation test, the test specimen is crushed (destroyed) when the test is performed. Therefore, only one test can be performed on one test specimen, and multiple tests cannot be performed on the same test specimen. On the other hand, the cone plunger test of the present invention makes it possible to perform multiple tests on one test specimen by changing the penetration point of the cone into the test specimen (shifting the penetration point).

[0051] In this way, since there is no need to prepare a test specimen each time a test is performed in the self-supporting property evaluation process or the pumpability evaluation process, the tests can be performed easily. Furthermore, when evaluating the self-supporting property over time after mixing, the same test specimen can be used for the test, which eliminates errors in the evaluation results due to variations in the test specimens and enables accurate evaluation. [Explanation of symbols]

[0052] 10 Cone plunger test machine 11 Foundation 12 Arm 13. Corn 14 Support rod 15 Jig 20 Samples

Claims

1. A method for evaluating properties of a composite material used to create an additive manufacturing object using a 3D printer, comprising: A pumpability evaluation step of evaluating pumpability, a self-supporting property evaluation step of evaluating self-supporting property, and a stacking property evaluation step of evaluating stacking property. Including, The pumpability evaluation step includes performing at least one of a table flow test and a cone plunger test, and evaluating the pumpability of the composite material based on whether or not the test result is within an appropriate value range; The self-supporting property evaluation step includes carrying out a cone plunger test to evaluate the self-supporting property of the composite material based on whether or not the test result is within a range of appropriate values; The lamination property proper evaluation step includes determining an arithmetic mean roughness of the surface property of the layered object, and evaluating the lamination property of the composite material based on whether or not the arithmetic mean roughness is within a proper value range. A method for evaluating the properties of a material used in an additive manufacturing object created by a 3D printer.

2. The pumpability evaluation step evaluates the fluidity of the material by at least one of a table flow test and a cone plunger test, and evaluates the pumpability of the composite material based on the test value. A method for evaluating the properties of a material used in a layered object created by the 3D printer according to claim 1.

3. The self-supporting property evaluation step includes determining a yield stress of the layered object by a cone plunger test, and evaluating the self-supporting property of the composite material based on the yield stress. A method for evaluating the properties of a material used in a layered object created by the 3D printer according to claim 1 or 2.

4. The stackability evaluation step includes: recognizing a cross-sectional shape of the layered object to obtain an arithmetic mean roughness; and evaluating the stackability of the composite material based on the arithmetic mean roughness. A method for evaluating the properties of a material used in a layered object created by the 3D printer according to any one of claims 1 to 3.

5. The stackability evaluation step evaluates the stackability of the composite material by taking into account an evaluation value of the aesthetics of the cross-sectional shape of the layered object. A method for evaluating the properties of a material used in a layered object created by the 3D printer according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • High-thixotropy 3D printing cement-based material and preparation method and application thereof

    CN112125618A

  • Cement composition for molding and manufacturing method of cement hardened body

    JP2017024979A

  • Three-dimensional modeling cement composition for construction, and three-dimensional modeling method for construction

    JP2018140906A

  • Three-dimensional (3D) printer nozzle device, 3D printer apparatus, method of constructing building structure using the same, method of feeding viscous material, and produced product constructing apparatus

    JP2019147338A

  • Multi-component mortar

    JP2019536725A